HUBUNGAN HIGIENE SANITASI KONDISI DEPOT AIR MINUM DENGAN KUALITAS MIKROBIOLOGIS AIR MINUM ISI ULANG DI KECAMATAN BANYMANIK SEMARANG - Hayati Era Novroza; Retno Hestiningsih; Nissa Kusariana (Jurnal Kesehatan Masyarakat (Undip), 2020)
Refill drinking water has attracted many people, one of them is Banyumanik sub-district. After a preliminary study, the results obtained from 5 AMIU samples 100% containing colifrom bacteria and 3 samples including E. coli bacteria. Based on Permenkes No. 492 / MENKES / IV / 2010 that the microbiological parameters of safe drinking water are the maximum levels of total Coliform and E.coli levels of 0 per 100 mL sample. If drinking water contained Coliform and E.coli bacteria will cause diarrheal disease. The purpose of this study is to analyze the relationship of sanitary hygiene with microbiological quality in refill drinking water in Banyumanik District. This type of research is observational analytic with cross sectional study approach. The research sample consisted of 35 refill drinking water samples. Data analysis using Fisher Exact. Refill drinking water mostly did not meet health requirements based on Colifrom status and was contaminated with Escherichia coli by 27 samples (77.1%). There is a relationship between hand hygiene (p = 0.018) with microbiological quality in refill drinking water. There was no relationship between DAM hygiene (p = 0.648) and equipment hygiene (p = 0.101) with microbiological quality in refill drinking water. Appeals are needed in the supervision of DAM and examination of samples as well as educational efforts with WHO hand washing poster media installed in drinking water depots.